PENGGUNAAN KECERDASAN BUATAN (ARTIFICIAL INTELLIGENCE) DALAM DUNIA PENDIDIKAN DI INDONESIA: TINJAUAN LITERATUR - Sihaloho, Fahmi Ashari S; Napitupulu, Zulhamdani (REKOGNISI : Jurnal Pendidikan dan Kependidikan (E-ISSN 2599-2260), 2024)
This study aims to examine the use of Artificial Intelligence (AI) in education in Indonesia through a systematic literature review (SLR) method. Based on the analysis of 15 journal articles published between 2018 and 2024, this research identifies various AI applications in education, including chatbots for science and engineering learning, social robots for religious education, and AI for learning evaluation. The results show that AI has great potential to improve the efficiency and effectiveness of learning, provide more personalized feedback, and assist educators in decision-making. However, AI implementation also faces challenges such as high costs, the need for technological infrastructure, and ethical issues. This research provides a comprehensive overview of the opportunities and challenges faced in integrating AI into education in Indonesia and offers recommendations for further research and development.